Radiation and chemical reaction effects on MHD flow along a moving vertical porous plate - Reddy, Gurrampati Venkata Ramana; Reddy, N. Bhaskar; Gorla, Rama Subba Reddy (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents an analysis of the effects of magnetohydrodynamic force and buoyancy on convective heat and mass transfer flow past a moving vertical porous plate in the presence of thermal radiation and chemical reaction. The governing partial differential equations are reduced to a system of self-similar equations using the similarity transformations. The resultant equations are then solved numerically using the fourth order Runge-Kutta method along with the shooting technique. The results are obtained for the velocity, temperature, concentration, skin-friction, Nusselt number and Sherwood number. The effects of various parameters on flow variables are illustrated graphically, and the physical aspects of the problem are discussed.
Keywords: MHD; porous medium; thermal radiation; heat transfer; mass transfer; chemical reaction